Is MENA a Region? The Scope for Regional Integration - Fischer, Stanley (International Monetary Fund, 1996)
The paper analyzes the scope and implications of greater economic integration in the Middle East and North Africa (MENA). After reviewing whether MENA satisfies the defining characteristics of a region, it documents the low level of regional economic interaction. It argues that gains from greater regional interactions will depend primarily on implementing domestic reform and external policies that, in any case, are needed for the region to benefit from the broader process of globalization of the world economy. It also discusses measures aimed directly at facilitating regional interaction